Initial Geochemical Assessment of Coaly Source Rocks in Sumatera, Java,and Kalimantan - Jyalita, Jasmin; Hendra A, Donatus; Anggara, Ferian (Journal of Applied Geology, 2023)
In Western Indonesia’s petroleum system, one of the hydrocarbon source rocks was deposited in parallic-deltaic environment with high organic content, categorizing it as coaly source rock. This study focused on geochemical characteristics of 25 coal and coaly shale samples from rock outcrops and well representing the Central Sumatra, South Sumatra, South Central Java, Barito, and Kutai Basin, with additional data from previous studies. TOC analysis and Rock-eval Pyrolysis were carried out to reveal the geochemical characteristics and maturation pathway of the source rock. The TOC analysis results showed a value of 0.5-67.73 wt%, indicating poor-excellent source rock potential. Further rock-eval pirolysis exhibits kerogen type II/II-III (excluding samples from Ngimbang Fm.), with gas-dominated hydrocarbon. Hydrocarbon Index ranging from 4-308 mg/gC indicates possible low-moderate quantity of hydrocarbon that can be generated by the source rocks. Despite the overall fair-good source rock potential, Tmax of the samples indicates a very poor maturity level, with only Upper Talang Akar as the mature candidate. Thus, it can be concluded that young source rock candidates in Western Indonesia (limited to the basins studied in this research) initially possess potential in generating hydrocarbons, if it is not for the immature level of most coaly source rock formations.